Evaluasi Etika Kebijakan Pengentasan Kemiskinan di Kabupaten Bima: Menjaga Dignitas dan Kesejahteraan Masyarakat - Wawan Mulyawan (Universitas 17 Agustus 1945 Semarang, 2024)
The aim of this study is to explore the ethical principles applied in the process of creating and implementing poverty alleviation policies in Kabupaten Bima, utilizing a qualitative descriptive approach. Informants were selected purposively, involving key figures such as government officials from the Social Services and Regional Development Planning Agency (Bappeda) of Kabupaten Bima, academics, and community activists, to gather data through in-depth interviews, participatory observation, and document analysis. The findings indicate that the success of these policies heavily depends on the implementation of transparency, distributive justice, and accountability. Transparency ensures that the policy process can be followed and monitored by the public, enhancing trust and community participation. Distributive justice promotes the fair allocation of resources, ensuring that all segments of society feel the benefits of the implemented policies. Meanwhile, accountability underscores the government's responsibility in managing and reporting resources fairly and honestly. This research also highlights the importance of using information technology to support transparency and enhance community participation, as well as strengthening the capacities of both government and communities to create an ethical and effective poverty alleviation system.